Expertise of using striking techniques for power stroke in badminton - Zhu, Q. (Perceptual and Motor Skills, 2013)
Two striking techniques (fast swing and angled striking) were examined to see if they allowed effective use of string tension for the power stroke in badminton. 12 participants (4 novices, 4 recreational, and 4 expert badminton players) were recorded by a fast-speed camera while striking a shuttlecock with racquets of 8 different string tensions. The peak speed of the shuttlecock, the racquet angle and the shuttlecock angle were analyzed. The results showed that expert players succeeded in using both striking techniques to overcome the constraint of string tension and produce a consistently superior stroke. Failure to use either striking technique resulted in inferior performance that was constrained by string tension. Expertise in badminton allows the necessary motor adjustments based on the affordance perception of the string tension.